NATURE AND COLOR (WITH REFERENCE TO ENVIRONMENT): प्रकृति एवं रंग (पर्यावरण के सन्दर्भ में) - Pahadia, Bharti (International Journal of Research -GRANTHAALAYAH, 2014)
Innumerable mountains, trees, rivers, lakes, flowers, leaves, animals, birds or humans are just part of this nature. Man has expressed his aesthetic experience through art. According to Rabindranath Tagore - “The artist is Prakriti Parmi. Therefore, he has a slave as well as a lover. "Artists bring out the tones prevailing in nature and their effect, making the subtle study of abstract expressive object effected by the diversity of its effects. In this way, pictures and life come alive with the attraction of colors. Color has an important place in human life. Human attraction to colors has never decreased. That is why, from primitive cave dwellers to modern humans, color has taken advantage in the development of beauty. The colors have immense power to evoke the mental emotions of human beings. This wonderful world of colors is seen from the color arrangement of rooms to the color scheme of flowers and plants in gardens. Our nature is covered with colors. Wherever our vision falls in nature, it is situated with some color. On the one hand, the inner life of man is derived from the result of the external world, on the other hand, according to his mentality, the human being accepts the outer world, so the vision and The creation (nature) cannot be divided. Our sensitivities and human consciousness are directly related to the combination of colors. असंख्य पहाड़, पेड़, नदियां, झीलें, फूल-पत्तियां, पशु-पक्षी अथवा मानव मात्र इस प्रकृति के अंग है। मानव ने अपनी सौन्दर्यानुभूति को कला के माध्यम से व्यक्त किया है। रवीन्द्रनाथ टैगोर के अनुसार - “ कलाकार प्रकृति पे्रमी है। अतः उसका दास भी है और प्रेमी भी। ” कलाकार प्रकृति में व्याप्त रंगतों को एवं उनके प्रभाव को फलक पर उतारते हैं, अमूर्त अभिव्यंजनावादी वस्तु का सूक्ष्म अध्ययन का उसके प्रभावों का तूलिकाघातों के वैविध्य से प्रभावपूर्ण बनाते हैं। इस प्रकार रंगों के आकर्षण से चित्र और जीवन सजीव हो उठते हैं। मानव जीवन में रंग का महत्वपूर्ण स्थान है। रंगों के प्रति मानव का आकर्षण कभी घटा नहीं है। इसलिए तो आदिम गुहावासियों से लेकर आधुनिक मानव तक ने सौन्दर्य के विकास में रंग का सहारा लिया है। रंगों में मानव की मानसिक भावनाओं को उद्वेलित करने की असीम षक्ति निहीत है। रंगों का यह अद्भुत संसार कमरे की रंग व्यवस्था से लेकर बाग-बगीचों में फूल-पौधों की रंग योजना तक में देखा जाता है। हमारी प्रकृति रंगों से सरोबार है। हमारी दृष्टि प्रकृति में जहां कही भी पड़ती है वह कोई न कोई रंग लिए स्थित है।एक ओर मनुष्य का आंतरिक जीवन बाह्य जगत के परिणाम से निष्पन्न्न होता है तो दूसरी ओर मनुष्य अपनी मनोवृत्ति के अनुसार बाह्य जगत को ग्रहण कर लेता है अतः दृष्टि व सृष्टि (प्रकृति) का विभाजन नहीं किया जा सकता है। हमारी संवदनषीलता और मानवीय चेतना का सीधा सम्बन्ध रंगों के संयोजन से है।